2018
DOI: 10.11646/zootaxa.4397.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Systematics, distribution and ecological analysis of rodents in Jordan

Abstract: Distributional and ecological data were given to all rodents of Jordan. The rodent fauna of Jordan consists of 28 species with 20 genera in eight families (Cricetidae, Dipodidae, Gliridae, Hystricidae, Muridae, Myocastoridae, Sciuridae,and Spalacidae), including four introduced species.Keys for families and species were provided, along with diagnosis for each species and cranial illustrations for most species. Habitat preference and zoogeographic affinities of rodents in Jordan wereanalyzed, as well as their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 589 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Traps containing peanut butter and jam were set up at night and tested every morning for 1-3 d at each location before being moved to a new location within the same sampling range. Prior to DNA barcoding, species identification of animals during trapping relied on morphology, as previously described (Amr et al, 2018). At the time of collection, the weight and reproductive status of each animal were recorded.…”
Section: Rodent Trapping and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Traps containing peanut butter and jam were set up at night and tested every morning for 1-3 d at each location before being moved to a new location within the same sampling range. Prior to DNA barcoding, species identification of animals during trapping relied on morphology, as previously described (Amr et al, 2018). At the time of collection, the weight and reproductive status of each animal were recorded.…”
Section: Rodent Trapping and Samplingmentioning
confidence: 99%
“…Given the unusual existence of different bioclimatic regions in the GRV, the wildlife fauna is exceptionally diverse, with wild rodents comprising a substantial proportion (Amr et al, 2018). Rodents encounter various conditions in their natural habitats that affect their level of fitness.…”
Section: Introductionmentioning
confidence: 99%
“…The mesosinusid (between metaconid and entoconid) is directed forward in its labial part, almost isolating the metaconid when the teeth start to wear. The longitudinal ridges are less developed, and are slightly offset in young teeth (Baker and Amr 2003;Siahsarvie and Darvish 2007;Stoetzel et al al., 2011;Aouraghe and Haddoumi 2012;Geraads et al 2013;Amr et al 2018).…”
Section: Description and Comparisonmentioning
confidence: 99%
“…The only species of dormouse (Gliridae) living in Jordan is Eliomys melanurus (Amr et al 2018), and it was most frequently found in Petra as the prey of B. bubo (Al Baida), but also of S. butleri (Wadi Khariobsa). in Jordan, Israel and Syria (author's data).…”
Section: H U M E ' S O W L ( S T R I X B U T L E R I H U M E 1 8 7 8 )mentioning
confidence: 99%
“…Data on bats identified from owl pellets found in Jordan are published in the paper Benda et al (2011). Some of my unpublished results have been used in the latest survey of rodents in Jordan (Amr et al 2018). The incidence of mammal remains in owl pellets in Syria has been investigated by Shehab with regard to B. bubo (Shehab 2004) and T. alba (Shehab 2005(Shehab , 2006.…”
Section: Introductionmentioning
confidence: 99%